Phase II trial of delta-tocotrienol in neoadjuvant breast cancer with evaluation of treatment response using ctDNA - Ina Mathilde Kjær; Søren Kahns; Signe Timm; Rikke Fredslund Andersen; Jonna Skov Madsen; Erik Hugger Jakobsen; Tomasz Piotr Tabor; Anders Jakobsen; Troels Bechmann (Scientific Reports, 2023)
Abstract Neoadjuvant treatment of breast cancer is applied to an increasing extent, but treatment response varies and side effects pose a challenge. The vitamin E isoform delta-tocotrienol might enhance the efficacy of chemotherapy and reduce the risk of side effects. The aim of this study was to investigate the clinical effect of delta-tocotrienol combined with standard neoadjuvant treatment and the possible association between detectable circulating tumor DNA (ctDNA) during and after neoadjuvant treatment with pathological treatment response. This open-label, randomized phase II trial included 80 women with newly diagnosed, histologically verified breast cancer randomized to standard neoadjuvant treatment alone or in combination with delta-tocotrienol. There was no difference in the response rate or frequency of serious adverse events between the two arms. We developed a multiplex digital droplet polymerase chain reaction (ddPCR) assay for the detection of ctDNA in breast cancer patients that targets a combination of two methylations specific for breast tissue (LMX1B and ZNF296) and one cancer specific methylation (HOXA9). The sensitivity of the assay increased when the cancer specific marker was combined with the ones specific to breast tissue (p < 0.001). The results did not show any association between ctDNA status and pathological treatment response, neither at midterm nor before surgery.